2016 Development effectiveness review. (Development effectiveness review., 2017)
Gross domestic product per capita growth eased to 5.8% across ADBs developing member countries (DMCs) in 2015 but was still far higher than in the rest of the world. Extreme income poverty has dropped as economies have grown and was down to 9% in 2013 from 12% in the previous year. If growth and other favorable conditions can be sustained, extreme poverty could be largely eradicated in the region by 2020. People gained greater access to vital infrastructure such as roads and electricity, and their use of formal banking services also grew. The 2015 Millennium Development Goal (MDG) targets on education were surpassed, and gender equality in access to education made large gains.